DIREITO DE RESISTÊNCIA E DESOBEDIÊNCIA CIVIL (REMUNOM, 2023)
The State is the supreme entity that establishes the legal rules necessary for individuals to live together in society. Therefore, if it is necessary that these norms must have coercive force, it is certain that they may not exclude fundamental rights and guarantees, at the risk of individuals being legitimized to oppose tyrannical power by means of civil disobedience, in the exercise of the right to resistance. These are legitimate instruments, which have arisen in different political and social contexts, and are present nowadays in the face of growing social movements. This article intends to analyze the right of resistance as an exercise of popular non-acceptance of legal norms that violate the fundamental guarantees of individuals, especially when facing anti-democratic states. It seeks to present the concepts necessary to understand the problem to be faced, with the necessary distinction between legal norms and social norms. It also discusses the relevant definitions and characteristics in order to understand the right of resistance. Then, it demonstrates its evolution with the civil disobedience, through the exercise, by minority groups, of lawful acts and with constitutional support, for the defense of moral rights, based, even if in general lines, on Ronald Dworkin's theory. It also analyzes decisions of the Federal Supreme Court on the legitimacy of social movements in the exercise of the right of resistance.